The Role of Job Demands, Work–Life Balance, and Psychological Safety in Shaping Generation Z Employee Productivity: Evidence from Jabodetabek - Kania, Awallya Restu; Rozamuri, Arif Murti (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2026)
This study examines the effects of job demands, work-life balance, and psychological safety on the productivity of Generation Z workers in the Jabodetabek region. Increasing work pressure, challenges in balancing professional and personal responsibilities, and psychological concerns among early-career employees have become important factors affecting productivity. Although previous studies have explored these variables separately, limited research has examined their combined influence on Generation Z workers. Therefore, this study aims to analyze how psychological and organizational factors interact to shape employee productivity. Using a quantitative approach, structured questionnaires were distributed to 109 Generation Z employees, born between 1996 and 2005, working in the Jabodetabek area. Data were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 3. The findings show that job demands, work-life balance, and psychological safety all have positive and statistically significant effects on employee productivity. Among these variables, psychological safety has the strongest influence. This study contributes to the literature on Generation Z productivity and offers practical insights for organizations seeking to create supportive and sustainable work environments for future human resource strategies, employee engagement programs, and long-term organizational performance across industries in urban Indonesia's labor market